2020
DOI: 10.1177/0037768620907566
|View full text |Cite
|
Sign up to set email alerts
|

Godly husbands and housework: A global examination of the association between religion and men’s housework participation

Abstract: In studies seeking to understand cultural and institutional influences on the division of domestic labor, religion has often been left out of the picture in favor of economic, gender and welfare state context. By examining men from 34 countries using 2012 International Social Survey (ISSP) data this study explores the ways in which religion is associated with men’s household labor participation. We utilize individual measures of religiosity as well as cultural zones based on religious and cultural similarity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…The religious fertility advantage is more than twice as great for progression from the second to the third child when comparing those with the lowest and highest salience or the least and most frequent attendance: more nominal religiousness (including mere affiliation) is more modestly associated with fertility. This is in keeping with recent work showing that nominally religious men do less housework than both highly religious and nonreligious men (Gull and Geist 2020). Thus while our analysis shows that the emergence of gender equity as the new natalism is not causing the religious fertility advantage to erode more quickly than otherwise expected, it supports the proposition that intensity of religion-not just religion-will matter for both future population size and religious shares of the future population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The religious fertility advantage is more than twice as great for progression from the second to the third child when comparing those with the lowest and highest salience or the least and most frequent attendance: more nominal religiousness (including mere affiliation) is more modestly associated with fertility. This is in keeping with recent work showing that nominally religious men do less housework than both highly religious and nonreligious men (Gull and Geist 2020). Thus while our analysis shows that the emergence of gender equity as the new natalism is not causing the religious fertility advantage to erode more quickly than otherwise expected, it supports the proposition that intensity of religion-not just religion-will matter for both future population size and religious shares of the future population.…”
Section: Discussionsupporting
confidence: 91%
“…Domestic tasks like diaper changing are not necessarily incompatible with religious concepts like "male headship" that undergo reinterpretation in more contemporary contexts, even among those fully devoted to the concepts (Denton 2004). While one study of the United States hinted that religious men's domestic involvement might be limited to childrearing activities (Ammons and Edgell 2007), more recent international work affirms that religious men's family-centeredness includes taking care of the house (Gull and Geist 2020).…”
Section: Gender Role Attitudes Religion and Fertilitymentioning
confidence: 99%
“…(stay-at-home order implemented by March 23, 5 used as reference group), early adopters (stayat-home order implemented between March 24-March 30), late adopters (stay-at-home order implemented after March 30), and resisters (no stay-at-home order issued). Within families, parental age(Gull and Geist 2020;Sanchez 1994), own and partners' health (ranging from 1=fair/poor to 4=excellent;Ross and Bird 1994), religious affiliation(Gull and Geist 2020), whether partners are married or cohabiting(Gull and Geist 2020;Kamo and Cohen 1998), child characteristics like youngest child's age and number of children(Kamo and Cohen 1998;Sanchez 1994), race/ethnicity(Maxwell and Solomon 2020;Pepin, Sayer, and Casper 2018; US Bureau of Labor Statistics 2020), and education(Davis and Greenstein 2004;Galinsky, Sakai, and Wigton 2011; Lachance-Grzela and Bouchard 2010) also likely shape parents' employment, earnings, work-family benefits, and changes in paid and unpaid labor.…”
mentioning
confidence: 99%
“…Petts (2018) found that fathers who take leave and attend religious services were more likely to be involved with their children than fathers who take leave but do not attend religious services. Gull and Geist (2020) found that increased religious participation was associated with men's greater participation in some housework tasks and time spent on housework, though the findings show great variation by task, religious tradition, level of religious attendance and across cultural zones. The research found that increased religious participation at the individual and cultural zone levels was associated with greater participation in some housework tasks and time spent on housework.…”
Section: Family Practices and Religious Identitymentioning
confidence: 90%
“…The role of religious values and their impact in contemporary societies continue to be the focus of researchers as both institutions go through the changes affected by modernization processes (Ammerman and Roof 1995;Ammons and Edgell 2007). The most recent research into the way religion and family institutions interact focuses on gendering practices and their impact on childcare and housework divisions (Goldscheider et al 2014;May and Reynolds 2018;Perales and Bouma 2019;Frenkel and Wasserman 2020;Gull and Geist 2020).…”
Section: Introductionmentioning
confidence: 99%